Coir Geotextiles for Paved Roads: A Laboratory and Field Study Using Non-Plastic Soil as Subgrade - M. K. Sayida; Sheela Y. Evangeline; M. S. Girish (Journal of Natural Fibers, 2020)
In this paper, pavement proposed on soft subgrade (SG) that requires improvement is studied and reported. One of the methods of improvement is reinforcing SG with geotextile. Laboratory studies were conducted on both paved and unpaved sections, whereas field performance studies were conducted only on paved roads. Three types of woven and one type of nonwoven coir geotextiles were used as reinforcement in the laboratory study, out of which one woven geotextile was used in the field. Effects of reinforcements were studied by placing the geotextiles at different positions of the section in the lab model, and cyclic load tests were conducted and resistance to permanent deformation was reported. Field performances were evaluated by the Benkelman beam deflection (BBD) test, the dynamic cone penetration (DCP) test, and the field California bearing ratio (CBR) test. Test results indicate that the reinforced roads have less distress compared to the unreinforced one. Change in characteristic deflection, DCP indices, and about 50% improvement in field CBR values were obtained for the reinforced one.